Design of a Dual Frequency Antenna for Energy Harvesting and WiMAX and WLAN Systems - Azidin, Mustika Rawiah; Yahya@Atan, Roshayati (Evolution in Electrical and Electronic Engineering, 2024)
In recent decades, alternative energy sources have gained increasing attention as the need for power increases. This increase occurred as external energy sources have been harvested for various purposes. The development of Wireless Local Area Networks (WLAN) and Worldwide Interoperability for Microwave Access (WiMAX) systems has grown more relevant and necessary in recent years. Due to the surge in demand for the development of alternative energy resources and WiMAX and WLAN systems, an antenna with dual frequency has been designed in this study. This antenna is designed to operate at 2.45 GHz and 3.7 GHz frequencies. The simulated antenna is analysed by its gain performance. The antenna design has undergone several phases including optimization levels and choosing the suitable antenna design to obtain the dual frequency and fulfil the chosen applications. FR-4 substrate is chosen as the antenna’s material. A microstrip patch antenna with a slotted gap technique is applied to increase the gain and obtain the desired frequencies of the antenna. CST Studio Suite Software is used in designing and obtaining the results for the antenna. The results obtained from this study are the values of S11, radiation pattern and gain. The gain obtained shows that the antenna has a positive gain of 2.45 GHz while obtaining a negative gain for a frequency of 3.7 GHz. Based on this analysis, it can be concluded that this antenna is operating well for energy harvesting applications. It needs improvement to operate at 3.7 GHz, to be utilized in WiMAX and WLAN systems.